2019
DOI: 10.1259/bjr.20190271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiomics tools for image analyses and clinical prediction in nasopharyngeal carcinoma

Abstract: Objective:Radiomics pipelines have been developed to extract novel information from radiological images, which may help in phenotypic profiling of tumours that would correlate to prognosis. Here, we compared two publicly available pipelines for radiomics analyses on head and neck CT and MRI in nasopharynx cancer (NPC).Methods and materials:100 biopsy-proven NPC cases stratified by T- and N-categories were enrolled in this study. Two radiomics pipeline, Moddicom (v. 0.51) and Pyradiomics (v. 2.1.2) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…Firstly, some features had significant association with H&N cancer overall survival in the IBSI-compliant software but not in IBEX. These findings concur with Liang et al who investigated two platforms and found differences in downstream clustering of known prognostic factors in patients with nasopharyngeal carcinoma [ 20 ]. Similar conclusions were drawn by Bogowicz et al who investigated this in PET scans of patients with H&N cancer [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, some features had significant association with H&N cancer overall survival in the IBSI-compliant software but not in IBEX. These findings concur with Liang et al who investigated two platforms and found differences in downstream clustering of known prognostic factors in patients with nasopharyngeal carcinoma [ 20 ]. Similar conclusions were drawn by Bogowicz et al who investigated this in PET scans of patients with H&N cancer [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have previously demonstrated that features can vary when calculated in different software platforms [18][19][20]. The Image Biomarker Standardisation Initiative (IBSI) is an international collaboration developed to help standardise radiomic feature calculation and has provided a framework to deliver practical solutions to this problem [21].…”
Section: Introductionmentioning
confidence: 99%
“…Yoon et al indicated that tumor features extracted through CT radiomics helped discriminate HER2-positive GC patients who had better survival rates and received trastuzumab-based treatment [22]. Radiomics is a recently proposed accurate prognosis prediction tool, but the complexity of feature extraction limits its unity in different centers [23]. The present study indicates that chemotherapy provided better survival benefits to patients with low splenic densities and diffusion tumor location.…”
Section: Discussionmentioning
confidence: 56%
“…The data source of radiomics is always obtained from retrospective medical imaging images. Different imaging techniques can lead to differences in image signals and image textures in medical imaging due to different acquisition parameters and reconstruction schemes [35][36]. If the parameters collected vary widely, this can introduce signal changes that are not caused by biological effects.…”
Section: Workflow Of Radiomics and Machine Learningmentioning
confidence: 99%